2021
DOI: 10.3390/ijms22052671
|View full text |Cite
|
Sign up to set email alerts
|

Magic Peptide: Unique Properties of the LRR11 Peptide in the Activation of Leukotriene Synthesis in Human Neutrophils

Abstract: Neutrophil-mediated innate host defense mechanisms include pathogen elimination through bacterial phagocytosis, which activates the 5-lipoxygenase (5-LOX) product synthesis. Here, we studied the effect of synthetic oligodeoxyribonucleotides (ODNs), which mimic the receptor-recognized sites of bacterial (CpG-ODNs) and genomic (G-rich ODNs) DNAs released from the inflammatory area, on the neutrophil functions after cell stimulation with Salmonella typhimurium. A possible mechanism for ODN recognition by Toll-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…These results suggested that MG-derived MG-H1 released by bone metastasis-derived PC3 cells reprograms human OB into a mesenchymal-, malignant-like phenotype through a RAGE-dependent mechanism. Importantly, upon MG-H1-containing PC3 CM exposure, blockade of RAGE with the high-affinity RAGE-specific inhibitor FPS-ZM1 [ 41 , 42 ], rescued OB dedifferentiation and re-wiring, evaluated by VIM, CADH11, Runx 2, CD44, migration, and PSMA levels ( Figure 11 d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested that MG-derived MG-H1 released by bone metastasis-derived PC3 cells reprograms human OB into a mesenchymal-, malignant-like phenotype through a RAGE-dependent mechanism. Importantly, upon MG-H1-containing PC3 CM exposure, blockade of RAGE with the high-affinity RAGE-specific inhibitor FPS-ZM1 [ 41 , 42 ], rescued OB dedifferentiation and re-wiring, evaluated by VIM, CADH11, Runx 2, CD44, migration, and PSMA levels ( Figure 11 d).…”
Section: Resultsmentioning
confidence: 99%
“…These results suggested that MG-derived MG-H1 released by bone metastasis-derived PC3 cells reprograms human OB into a mesenchymal-, malignant-like phenotype through a RAGE-dependent mechanism. Importantly, upon MG-H1-containing PC3 CM exposure, blockade of RAGE with the high-affinity RAGE-specific inhibitor FPS-ZM1 [41,42], rescued OB dedifferentiation and re-wiring, evaluated by VIM, CADH11, Runx 2, CD44, migration, and PSMA levels (Figure 11d). Overall, these findings indicated that MG-derived MG-H1 released by bone metastasis-derived PC3 cells reprogrammed human primary OB into a mesenchymal-, malignantlike phenotype through a RAGE-dependent mechanism with the involvement of ROS and NF-kB signaling.…”
Section: Mg-derived Mg-h1 Released By Bone Metastasis-derived Pc3 Cells Reprograms Human Ob Into a Mesenchymal- Malignant-like Phenotype mentioning
confidence: 98%